PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PERILAKU ORGANISASI - Eks Enus, Oriyanto; Dwikurnaningsih, Yari; Sugiarto, Agus (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This study explores the role of principals in enhancing organizational behavior in schools. Using a qualitative approach, the research examines five main aspects: organizational culture development, effective communication, teacher competency development, organizational challenges, and the influence of principal leadership on teacher motivation. The findings reveal that principals play a crucial role in creating a conducive work environment through effective communication, continuous training, and teacher recognition. However, challenges such as resistance to change and budget constraints require innovative approaches. This study concludes that effective principal leadership can improve teacher motivation and performance, ultimately contributing to the success of school organizations.